The Influence of Regional Original Income, General Allocation Funds and Regional Government Financial Performance on Capital Expenditures (Case Study in Districts and Cities in the South Sumatra Region) - Ika Setia Ningsih; Maulan Irwadi; Lukita Tri Permata (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine the effect of Local Own Revenue, General Allocation Funds and Regional Government Financial Performance on Capital Expenditures in districts and cities in the South Sumatra region. The object of this research is the district and city governments in the South Sumatra region, totaling 17 local governments and the research years from 2015 to 2019. The data used are secondary data and the research sample is a saturated sample because all research objects are sampled . The analysis technique uses multiple regression and the data is processed using SPSS software. The results showed that based on the simultaneous test, the variables of Regional Original Income, General Allocation Funds and Regional Government Financial Performance had a significant effect on capital expenditure. Based on the partial test, the variables of Regional Own-Owned Income and Regional Government Financial Performance as measured by the Level of Regional Wealth have a significant effect on Capital Expenditures while the General Allocation Fund variable has no significant effect on Capital Expenditures.